O fenômeno bullying em escolares do ensino fundamental - Silva, Gilene Fernanda [UNESP] (2015)
The bullying phenomenon is appearing more and more at the mass media. Vilence and prejudice grows rapidly among all social. Kicks, threatening, pushing, bad language, belongings stealing, ridiculing, at school or the internet, are bad jokes that can lead to hard consequences for those involved. Agressions happen always from the strong to the weak, figuring a power disparity. This study has seeks to characterize bullying at Basic Education schools. There is a database from a questionnaire drawn up by the researcher herself, which is based upon some researchers from this particular area. Some 309 students have participated, 142 males and 167 females, from 6th to 8th grade of Basic Education from two schools or the town of Bauru, SP - one of these schools is conducted by the city, the other is conducted by the State of São Paulo. Results show that 27% (n=84) from those students had already got involved in bullying episodes. There were identified 61 students playing the role of victims, 8 playing the role of agressive victims, and 15 aggressors. The more common type of abuse girls and boys have suffered is verbal bullying, appointed by 92% of girls and 84% of boys; follows the psychological aggressions, appointed by 70% of girls and 53% of boys. Physical aggressions were related by 46% of girls and 44% of boys, and material aggression were reported by 27% of girls and 16% of boys. Sexual bulling was the most disparate between both sexes, being referred by 38% of girls and 16% of boys. Even at a digital age, only 13% of girls and 12% of boys reported virtual bullying. All kind of bullying are performed moslty by boys, directly or indirectly, an information that is different from the actual literature - for various authors state that boys usually perform physical bullying more frequently (direct). But this research goes along with main researches in the field, once girls where the most afflicted by agressions. The classroom was the most...